All Days 2010
DOI: 10.2118/132795-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Oil Recovery and Carbon Dioxide Storage in Heavy Oil Reservoirs

Abstract: We study the design of enhanced oil recovery in heavy oil reservoirs combined with CO2 storage using field-scale reservoir simulation. We consider properties typical of fields offshore Trinidad and Tobago with oils whose density ranges between 940 and 1010 kg/m3 (9-18 degrees API). We first tune a three-parameter Peng-Robinson equation of state to match measured PVT data. We use experimental design to study the influence of oil properties, phase behavior and injection design on oil recovery and net CO2 storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This work assumed that the CO 2 and oil were first-contact miscible; in this case, we propose an injection design derived from a heavy-oil sample that is immiscible with the CO 2 . The relative permeabilities used in simulations were presented in previous work (Sobers et al 2010) on the basis of history matching of sandpack-flooding experiments performed by Dyer and Farouq Ali (1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work assumed that the CO 2 and oil were first-contact miscible; in this case, we propose an injection design derived from a heavy-oil sample that is immiscible with the CO 2 . The relative permeabilities used in simulations were presented in previous work (Sobers et al 2010) on the basis of history matching of sandpack-flooding experiments performed by Dyer and Farouq Ali (1994).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work (Sobers et al 2010), we found that carbon storage and heavy-oil recovery can occur simultaneously using water-alternating-gas (WAG) injection but are sensitive to fluidinjection rates. A closer look at the results revealed the dependence of oil recovery and carbon storage on the extent of the mixing zone, which in turn is a function of injection rate, water/gas ratio, and slug sizes.…”
Section: Introductionmentioning
confidence: 99%